ANALYSIS OF THE PROMOTIONAL ACTIVITIES OF KOSZALIN IN THE YEARS 2008-2013 (Research Bulletins of the Faculty of Economic Sciences, 2021)
Outline of the contents:The present article covers an analysis of the promotional activities undertaken by the town of Koszalin in the years 2008-2013. Among others, activities were presented within the framework of the economic promotion of the town and, in particular, in relation to the promotion of tourism (including the quantity of financial expenditures for the promotion of the town in the years 2008-2013, examples of the instruments of promotion used, examples of the cooperation of Koszalin with partner towns). A part of the study was devoted to an analysis of the promotional activi-ties undertaken by the Central Pomeranian Districts and Communes Associationas an institution that supports the town’s activities of in this area.
Keywords: economic promotion,promotion of tourism, Koszalin